(untitled) (Bangladesh Journal of Agriculture, 2022)
The study aims to know the scenario of duckling production using rice husk incubator and socio-economic status of the farmers of Vatiapara village under Baniachang upazila of Habiganj District. A total of 140 number of households were interviewed among them 64.7% family had homestead land followed by 35.3% family had both homestead and cultivated land. All living houses were of tin made with 70% nuclear and 30% joint family. There about 9.1% illiterate and 39.4% people could sign only. The primary, secondary and higher secondary or upper educational levels were 25.7%, 18.2% and 7.6%, respectively. More than 76.5% family are engaged directly in duckling production whereas 23.5% family are involved in catching and cultivating fish. About 23.5% families were fully occupied in fisheries and 41.25% family in integrated agriculture as secondary occupation. On an average, their income was 10,676 Tk. Among the selected families 59% got training on duck rearing with hatchery management. Based on 70% hatchability, per family produced monthly more than 7000 number of ducklings from 10000 number of hatching eggs. The yearly turnover is calculated as to nine months hatching operation since the enterprise remained almost stop from the late November to mid-February. Hatching egg price was different due to seasonal variation and, on an average, it was 10.50 Tk. Overall 7088 number of ducklings were produced per household monthly, which valued about 177200 Tk. (25 Tk./duckling) and net profit was 66535 Tk./month. Thus, the community-based duckling production can be encouraged more among the families through providing an adequate technical knowledge, training and an improvement of marketing channel to increase socio-economic status of the farmers. Bangladesh J. Agri. 2022, 47(1): 113-120